Safety and immunogenicity of the candidate tuberculosis vaccine MVA85A in West Africa. - Roger H Brookes; Philip C Hill; Patrick K Owiafe; Hannah B Ibanga; David J Jeffries; Simon A Donkor; Helen A Fletcher; Abdulrahman S Hammond; Christian Lienhardt; Richard A Adegbola; Helen McShane; Adrian V S Hill (PLoS ONE, 2008)
Vaccination with a recombinant modified vaccinia Ankara expressing antigen 85A from Mycobacterium tuberculosis, MVA85A, induces high levels of cellular immune responses in UK volunteers. We assessed the safety and immunogenicity of this new vaccine in West African volunteers.We vaccinated 21 healthy adult male subjects (11 BCG scar negative and 10 BCG scar positive) with MVA85A after screening for evidence of prior exposure to mycobacteria. We monitored them over six months, observing for clinical, haematological and biochemical adverse events, together with assessment of the vaccine induced cellular immune response using ELISPOT and flow cytometry. MVA85A was well tolerated with no significant adverse events. Mild local and systemic adverse events were consistent with previous UK trials. Marked immunogenicity was found whether individuals had a previous BCG scar or not. There was not enhanced immunogenicity in those with a BCG scar, and induced T cell responses were better maintained in apparently BCG-naïve Gambians than previously studied BCG-naïve UK vaccinees. Although responses were predominantly attributable to CD4+ T cells, we also identified antigen specific CD8+ T cell responses, in subjects who were HLA B-35 and in whom enough blood was available for more detailed immunological analysis.These data on the safety and immunogenicity of MVA85A in West Africa support its accelerated development as a promising booster vaccine for tuberculosis.ClinicalTrials.gov NCT00423839.